Enhancing Forensic Identification by Performing a Thorough Examination of Palatal Rugae Patterns in Over 200 Individuals through Palatal Rugoscopy (Journal of Forensic Medicine & Toxicology, 2026)
The application of palatal rugoscopy as a forensic identification technique is examined in this study. The study examines  the uniqueness, stability, and possibility for estimating age and gender in the palatal rugae patterns of more than 200  individuals. Digital photography, statistical analysis, cast preparation, and impressions taking are all part of the approach.  The findings shed light on age-related variances, gender-based disparities, and the frequency distribution of rugae types.  The discussion examines the implications for forensic science and assesses the main findings in light of the body of current research. The research is summed up, its importance is emphasized, and future research directions are suggested in  the conclusion.
Keywords: Palatal Rugoscopy; Palatal Rugae, Digital Photography; Statistical Analysis; Cast Preparation; Impressions; Age-related Variance; Gender-based Disparities; Frequency Distribution